Kafka, and the Decline of the Animal Metaphor. Notes on the Narrative Voice in “Investigations of a Dog” (Anclajes, 2011)
Franz Kafka’s animal stories are contemporary with the first philosophic questionings of the so-called metaphysics of subjectivity. This paper proposes an examination of that synchronism through an analysis of the narrative voice in the story “Investigations of a Dog”. We start, on one hand, from the hypothesis that, in this story, it is possible to find a particular way of thinking about animals and animality, one that is linked to the task of taking the animal metaphor apart; and, on the other hand, from the idea that this thought enables a dialogue with the reflections of Post-humanist philosophy, that is oriented towards the creation of a non-anthropocentric theoretical perspective.
Keywords: metaphor; animal; posthumanism; Franz Kafka; Investigations of a dog